The effects of okadaic acid-treated SH-SY5Y cells on microglia activation and phagocytosis - Prateep Amonruttanapun (2022)
The activation of microglia is found to be associated with neurodegenerative disorders including Alzheimer's disease (AD). Several studies have shown that okadaic acid (OA) induced deposition of tau hyperphosphorylation, and subsequent neuronal degeneration, loss of synapses, and memory impairment, all of which resemble the pathology of AD. Although OA is a powerful tool available for mechanisms of the neurotoxicity associated with AD, the exact mechanism underlying the activation of microglial cells remains unrevealed. The aim of this study was to determine the effect of both OA and OA-treated neuroblastoma SH-SY5Y cells on microglial HAPI cell viability, activation, and phagocytosis. The results showed that both OA and OA-treated neurons did not induce any detectable cytotoxicity of microglial cells. Furthermore, incubation with OA-treated SH-SY5Y cells could increase the expression of ionized calcium-binding adapter molecule 1 (Iba1) on microglial HAPI cells. This result indicated that OA may induce microglial activation through the toxicity of neurons. Moreover, we also demonstrated that OA-treated SH-SY5Y cells were engulfed by CD11b/c-labeled microglial HAPI cells, which were abolished after treatment with 10 mM O-phospho- l-serine (L-SOP) for 30 min before co-culture with OA-treated SH-SY5Y cells, indicating cells experiencing phagocytic activity. We also confirmed that OA treatment for 24 h significantly increased tau hyperphosphorylation at S396 in SH-SY5Y cells. In conclusion, our findings indicate that OA is a potential toxic inducer underlying the role of microglia in AD pathogenesis.